Revuelta social y nueva constitución - Richard, Nelly (Biblioteca Masa crítica CLACSO, 2021)
In October 2019, the slogan "Chile woke up" marked the people's desire to reappropriate a vital force stolen from the post-dictatorship neoliberal pact. Nelly Richard reviews the vertiginous itinerary that went from jumping the subway turnstiles to the formation of a Constituent Convention responsible for drafting a new constitution in 2021 to ask how to channel the vital energies of the revolt into certain transformative grammars that affect the redesign of democracy.The Masa Crítica library makes available to readers a set of essential texts to interpret the ribs of the present and deploy the collective capacities to transform it.